Environmental Pollutants in the Mediterranean Sea: Recent Trends and Remediation Approaches - El-Sayed Ali, Tamer (Bentham Science Publishers, 2023)
Pollution of the aquatic environment is a real threat across the globe. It is becoming a topic of intense study for researchers. It has been updated and almost completely revised. The Mediterranean Sea has been recognized as a target hotspot of the world as the pollutant concentration in this region is greater than the levels in other oceans. The book summarizes research on marine pollutants in the Mediterranean Sea. It presents 5 concise reviews focusing on microplastics, rare earth elements and biotoxins & which are now commonly found in the region. The Editors also emphasize on pollution problems in the Mediterranean region, with 2 chapters presenting studies on Lebanon and Morocco, respectively. The book adds to the collective information on Mediterranean marine pollution. Additionally, references are included at the end of each chapter for the benefit of advanced readers. The contributions also include discussions on important techniques used to monitor and control marine pollution, such as the bio-monitoring of effluents, and ecological impact assessment of microplastic pollution on fish and the environment.